2019
DOI: 10.17126/jor.v0i0.771
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of ceramic thickness and adhesive type on the de-bonding strength of dental ceramic veneers using Er,Cr:YSGG laser.

Abstract: Resumen: Propósito: La resistencia de desunión de las carillas de cerámica mediante el uso del láser debe evaluarse en detalle. El objetivo de este estudio es determinar la contribución del espesor de la cerámica y los agentes de cementación a la resistencia de desunión de las carillas de cerámica utilizando el láser Er, Cr: YSGG. Métodos: Un total de 120 incisivos centrales maxilares se dividieron al azar en doce grupos según el grosor del disco, el agente de cementación y el uso del láser Er, Cr: YSGG. En co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This came in agreement with other studies. Yilmaz et al 1 (2019) used 120 IPS Empress II discs of three different thicknesses (0.5 mm , 1 mm, 2 mm) and found that during laser debonding, the 2 mm discs needed more debonding force than the 1 mm and 0.5 mm and that all the 0.5 mm discs were debonded without any external load during the laser exposure. Giraldo Cifuentes et al 27 (2020) tested four different thicknesses (0.4 mm, 0.8 mm, 1.2 mm and 1.6 mm) and concluded that the thicker veneers demonstrated greater resistance to debonding than the thinner ones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This came in agreement with other studies. Yilmaz et al 1 (2019) used 120 IPS Empress II discs of three different thicknesses (0.5 mm , 1 mm, 2 mm) and found that during laser debonding, the 2 mm discs needed more debonding force than the 1 mm and 0.5 mm and that all the 0.5 mm discs were debonded without any external load during the laser exposure. Giraldo Cifuentes et al 27 (2020) tested four different thicknesses (0.4 mm, 0.8 mm, 1.2 mm and 1.6 mm) and concluded that the thicker veneers demonstrated greater resistance to debonding than the thinner ones.…”
Section: Discussionmentioning
confidence: 99%
“…An initial cure of 1 s. from each side of the disc with the LED curing light was applied to remove excess cement. The final cure of the cement was accomplished afterwards with a 20 s. light-cure with the curing light in contact with the glass slide and figure (1) shows the completed cemented disc. Finally, the samples were stored in distilled water and stored at 37°C for 24 h. prior to the debonding procedure 16 .…”
Section: Discs Cementationmentioning
confidence: 99%
See 2 more Smart Citations
“…10 When veneer removal is dictated, the conventional way is achieved by using traditional instruments with mechanical force, such as crown tractors, chisels, manual or automatic removers, 11 or a rotary instrument using a diamond bur to grind the veneer. 12 Although veneer debonding by grinding is complete, it is timeconsuming and associated with patient discomfort, and the underlying tooth structure may be affected due to friction, heat, vibration, and the integrity of the veneers being compromised. 13 Another factor to be considered is the difficulty of differentiating the veneer margin from the tooth structure due to the high aesthetic standard of modern restorative materials, leading to excessive tooth structure loss during veneer removal.…”
Section: Introductionmentioning
confidence: 99%